Enhancing Energy-Efficient Building Literacy Through Education and School Environment Identification Among Vocational High School Students - Sarwa Sarwa; V. Lilik Hariyanto; Ridho Azahar; Daniel Ngolu Jiledo Maringga (Universitas Malahayati Lampung, 2026)
ABSTRACT The building sector contributes significantly to energy consumption; therefore, literacy regarding energy-efficient buildings needs to be strengthened from the school education stage onwards. This study aims to analyse improvements in understanding and the ability to identify energy-efficient buildings within the school environment. The study employed an educational-participatory approach with a single-group pre-test–post-test design. The research sample consisted of 30 Year 10 students from the Construction and Housing Technology Department at SMK Negeri 1 Percut Sei Tuan. The activities were carried out over four sessions, comprising the delivery of material, discussions, a pre-test, a post-test, and practical exercises in identifying aspects of natural lighting, ventilation, lighting usage, and user behaviour. Data were analysed using descriptive statistics and a paired-samples t-test. The results showed that the mean score increased from 46.80 to 80.43, with the pass rate rising from 0% to 86.67%. Meanwhile, the practical assessment achieved a mean score of 81.90 with a 100% pass rate. The paired-samples t-test revealed a significant difference (p 0.001) between initial and final knowledge. The research findings indicate that education based on direct observation is effective in improving students’ literacy and practical skills regarding the knowledge and identification of energy-efficient buildings. Keywords: Energy-Efficient Buildings, Vocational Education, Participatory Learning, The School Environment.